Proportional distribution method for estimating actual grain flow under combine harvester dynamics - He, Wang; Xiaoping, Bai; Hongbin, Liang (International Journal of Agricultural and Biological Engineering, 2017)
The yield monitors use a constant delay time to match the grain flow with location. Therefore, mixing and smoothing effects on the grain flow are neglected. Although constant time delay compensates for time mismatch, actual grain flow at a combine harvester head is not equal to the grain flow measured by a sensor due to the dynamics effects. In order to eliminate the dynamics effects, a new method for estimating actual grain flow, called proportional distribution (PD), is proposed. This method assumes that actual grain flow is directly proportional to the feedrate. Based on this assumption, the actual grain flow results from redistributing accumulated grain mass over a certain time according to the profile of the feedrate. The PD can avoid the dynamics effects because the feedrate is measured at a combine harvester’s head. Compared with constant time delay, the proposed method can effectively estimate actual grain flow and be applied to improve the accuracy of yield maps.Keywords: grain flow, combine harvester, estimation method, proportional distribution, time delay, yield map, yield monitoring sensorDOI: 10.25165/j.ijabe.20171004.2732Citation: Wang H, Bai X P, Liang H B. Proportional distribution method for estimating actual grain flow under combine harvester dynamics. Int J Agric & Biol Eng, 2017; 10(4): 158–164.